THE ROLE OF NEEDLE IN FORMULATION OF pH SENSITIVE SWELLABLE MICROBEADS PREPARED WITH HYDROPHILIC POLYMERS FOR ATORVASTATIN AND THEIR CHARACTERIZATION STUDIES - Reddy, K.v. Ramana; Nagabhushanam, M. V. (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of the study was to develop and characterize mucoadhesive microbeads for oral sustained release of atorvastatin by using hydrophilic polymers and application of different process variables in designing of pH sensitive swellable microbeads. Methods: Microbeads were prepared by ionic gelation method. The compatibility studies of atorvastatin with polymers were investigated by differential scanning calorimeter and fourier transform infrared spectroscopy studies. In this work process variable like optimization of curing agents and their quantity, effect of rpm, and their influence in drug entrapment were studied. Prepared beads were characterized for particle size, swelling index, erosion studies and drug release studies. Results: Mixture of alginate and carbopol 934 P at 3.3 % w/v shows sustained release and good mucoadhesive capacity. Furthermore, drug loading and swelling increased with the use of a combination of polymers. On basis of in vitro release studies and swelling studies, it was observed that sodium alginate coated with carbopol 934 P showed sustained release of 84.5 % at end of 10 h in 6.8 phosphate buffer. The optimised batch followed peppas and higuchi release mechanism and releasing the drug by non-fickian transport. Conclusion: The alginate beads with a combination of carbopol 934P showed a sustain release pattern. The release rate and swelling of atorvastatin beads could be adjusted by adding other hydrophilic polymers or by optimising curing agents, curing time and their volume. The zero order of drug release was confirmed for all the batches. The in vitro data was better fit to Higuchi's diffusion model and diffusion rate limited.